Kinerja Guru Era 4.0: Kepemimpinan dan Motivasi - Romdah Romansyah (Departement of Mathematics Education, 2023)
The main problem examined in this study that the performance of teachers of Madrasah Aliyah Affairs as Ciamis district does not meet the standards expected. It is expected, among others, influenced by the leadership that is less democratic principals and teachers who are weak motivation. Based on this problem, the problem of the research will be limited, that is how big the contribution of leadership of school principals and teachers on the performance of teachers' motivation research was conducted in a district MAN Ciamis. The object of his research, among other variables headmaster (X1), teacher motivation variable (X2), and Teacher Performance 4.0 (Y). The formulation of the problem in this study werehow large the contribution of principal leadership and motivation of teachers together to Performance teacher in a district Ciamis MAN? The purpose of this study were to find out how big the contribution of principal leadership and motivation of teachers together to Performance MAN teacher in a district of Ciamis. The method used analytical descriptive method and data collection using a questionnaire. Sampling as many as 73 people. The results obtained following conclusion. There signitifikan contributions between principal leadership and motivation of teachers to performance, namely the higher the leadership of school principals and teachers'motivation will be higher the performance of teachers 4.0, on the contrary, if the leadership of school principals and teachers' low motivation will lead to decreasing performance of teachers.